Effects of methionine and tryptophan on some economic characters in the mulberry silkworm Bombyx mori L - Laz, Rezina; Gani, Ataul; Reza, AM Saleh (University Journal of Zoology, Rajshahi University, 2007)
Methionine and tryptophan were supplemented with food at four concentrations viz. 250, 500, 750 and 1000 ppm to evaluate the effects of these amino acids on the larval and pupal weight and different cocoon characters in the mulberry silkworm, Bombyx mori L. Treatments significantly enhanced the performance of all the parameters in both parental and F1 generations except the filament denier. Significant differences were also observed between the generations of all the parameters except the filament length. However, the highest concentration (1000 ppm) of both the compounds decreased the growth parameters in comparison to control. Key words: Bombyx mori, methionine, tryptophan, growth, filament length Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.57-62